Racial Identity And Otherness In Octavia E. Butler's Kindred - Baffi, Haifa; Benzoukh, Halima (جامعة الوادي - University of Eloued, 2022)
Abstract: The purpose of the present study is to understand how racial identity and otherness have been presented in the work of Octavia E. Butler's Kindred and how Black women in the USA struggled to develop the Self. Kindred is a time-traveling narrative and a story of Dana, who is a Black woman who discovers her ancestors' sufferance and recognizes how people of color experienced oppression and racism. African American literature accompanies Black women's journey to construct their identity through history. Black feminism theory and intersectionality are used to provide a range of black woman perspectives and explore the truth of woman identity intersections. By drawing on these theories, we attempt to shed light on the representation of black woman identity through Black female characters and discover the reality of Black women's otherness between the past and the present.
articl
Keywords: Black feminist theory ; black women ; female character ; otherness ; racial identity